Clinical lipidomics in the era of the big data - Kvasnička, Aleš; Najdekr, Lukáš; Dobešová, Dana; Piskláková, Barbora; Ivanovová, Eliška; Friedecký, David (Clinical chemistry and laboratory medicine, 2023)
Lipidomics as a branch of metabolomics provides unique information on the complex lipid profile in biological materials. In clinically focused studies, hundreds of lipids together with available clinical information proved to be an effective tool in the discovery of biomarkers and understanding of pathobiochemistry. However, despite the introduction of lipidomics nearly twenty years ago, only dozens of big data studies using clinical lipidomics have been published to date. In this review, we discuss the lipidomics workflow, statistical tools, and the challenges of standartisation. The consequent summary divided into major clinical areas of cardiovascular disease, cancer, diabetes mellitus, neurodegenerative and liver diseases is demonstrating the importance of clinical lipidomics. In these publications, the potential of lipidomics for prediction, diagnosis or finding new targets for the treatment of selected diseases can be seen. The first of these results have already been implemented in clinical practice in the field of cardiovascular diseases, while in other areas we can expect the application of the results summarized in this review in the near future.
Keywords: big data; metabolomika; lipidomika; nádory; Lipidomics; biologické markery; lidé; Big Data; Neoplasms; Metabolomics; Humans; Biomarkers; metabolismus lipidů; Lipid Metabolism